Microbial influencers: treating diabetes through the gut. Issue 6 (8th June 2022) - Snelson, Matthew; Rampanelli, Elena; Nieuwdorp, Max; Hanssen, Nordin MJ; Coughlan, Melinda T
Abstract : A recently published study by Bell et al. shows altered immunotolerance in people with type 1 diabetes by dietary supplementation of modified resistant starch fibre.